Full-stack MQTT-based IoT system using two-tier networking - Chwa, Guang Yao (2025)
This project investigates the creation of a two-tier wireless mesh network (WMN) framework specifically designed for Industry 4.0 applications, with the goal of improving network stability, scalability, and cost-efficiency in industrial environments. The Fourth Industrial Revolution, often known as Industry 4.0, aims to disrupt traditional industrial processes by merging sophisticated technologies such as the Internet of Things (IoT), cyber-physical systems, and cloud computing. A strong and efficient network infrastructure capable of supporting a wide range of industrial applications is key to this integration. The current reliance on traditional star topologies and wired networks presents significant limitations, including single points of failure, limited scalability, and high deployment costs. This project addresses these challenges by implementing a WMN that eliminates single points of failure and adapts to dynamic factory floor environments. The proposed two-tier WMN consists of a backbone network of sink nodes and a secondary network of routers, employing dynamic routing algorithms to minimize the impact of network disruptions. Through a comprehensive review of existing wireless networking technologies and protocols, such as B.A.T.M.A.N. on ESP32 platforms, this project highlights the potential of WMNs to overcome existing network limitations. Although prior studies (e.g., [23]) evaluated BATMAN-adv on ESP32 platforms, this project applies the approach using ESP8266 devices, which are more cost-effective and sufficient for proof-of-concept. The project scope includes the implementation of a 2-tier dynamic routing mesh network within the edge tier of IoT applications, focusing on reliability and network operability. The results demonstrate a scalable, cost-effective, and robust network solution suitable for Industry 4.0, aligning with national policies aimed at advancing the manufacturing sector.